Customers’ satisfaction: factors affecting online shopping during COVID-19 pandemic / Amirudin Mohd Zani ... [et al.] - Mohd Zani, Amirudin; Ngah, Nazlin Emieza; Mohamad, Zuraida; Mohammad, Nurul Izani; Abd Aziz, Najdah; Dato’ Haji Setia, Roszainora (Universiti Teknologi MARA, Perlis, 2024)
Shopping is now easier and more accessible than ever in today’s hurried and connected society. This study was conducted to find out the factors influencing customer satisfaction in online shopping during COVID-19. Some barriers have contributed to the unwillingness of Malaysians because they worry others will take their personal information. Two factors were analyzed in this research, which are Information Quality and e-Service Quality, with a sample size of 150 respondents, and a convenience sampling method was used. A set of questionnaires was distributed online through Google Forms by sharing links in WhatsApp and email. Then, the data is analyzed using Statistical Package for Social Science (SPSS). The result showed that Information Quality and e-Service Quality have different relationships with customer satisfaction in online shopping. The limitations of this study are that the variables may not be sufficient, and there should be more variables to be considered in future research that may have a more significant impact. This study contributes to the realization that customer happiness is the most important factor to prioritize to improve a company’s favourable reputation in the marketplace